A study of preoperative, intra-operative and postoperative factors responsible for postoperative wound infection - Nisale, Shobha S.; Chawada, Meghraj; Kharkate, Ganesh K.; Deshmukh, Sudhir B. (International Surgery Journal, 2017)
Background: Many factors affect the incidence of surgical wound infection, in addition to the surgeon’s skill and the hospital environment. Host attributes, such as age over 60 years, diabetes mellitus, malignant disease, obesity, malnutrition, length of preoperative stay or pre-existing infection may influence risk, as may such operation characteristics as site, urgency, duration and time of skin shaving. Objective was to study the preoperative, intra-operative and postoperative factors responsible for postoperative wound infection. Methods: This descriptive study was designed to study the problem of postoperative wound infection at tertiary health care center at rural set up over a period of two years during 2014 to 2016. Initial assessment of intra operative findings divided these cases into clean, clean contaminated and contaminated cases. Results: As the length of pre-operative stay increased, the occurrence of SSIs increased. As the duration of post operative hospital stay increased, the occurrence of SSIs also increased. The occurrence of SSI increased as the quality of surgical wound deteriorated. As the duration of surgery increased, the occurrence of SSIs increased. It was found that the order of surgery was not related to occurrence of SSIs. It was found that the rate of SSI was more (21.55%) when the drain was used in comparison to only 8.04% when the drain was not used. The most common organism found to cause SSIs was staphylococcus aureus in 33.07% of cases. Conclusions: Slightly low incidence of SSIs in our study may be attributed to the better infection control practices though it must be concluded that more stringent aseptic measures including rational antibiotic policy will be contributory in lowering the SSI rate further.